1959
DOI: 10.1007/bf01800678
|View full text |Cite
|
Sign up to set email alerts
|

The structure of New Zealand from seismic evidence

Abstract: The New Zealand region is characterised by a crust 20--25 kms in thickness, and a sub-crust extending to at least 370 kms. These are separated by a transition layer extending from the base of the crust to a depth of about 100 kms. The crust is divided into blocks by steeply dipping faults. Some blocks are seismically active and others stable. The region is bounded by the Pacific Basin to the east, and the Tasman Basin to the west. Both of these areas have oceanic crusts about 5 kms thick. The sub-crust is trav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

1959
1959
1995
1995

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 9 publications
2
13
1
Order By: Relevance
“…The reduction of this figure would demand either a reduction of the mean density of (he crust by at least 0-3 g/cm 3 , or a comparable reduction of the mean density within the upper mantle. However, the longitudinal wave velocities in the upper part of the crust as well as P n for the material immediately below the crust appear to be similar to those found in other continental areas of rhe world, though the velocity of 6-2 krnysec for Eiby's «intermediate" layer lying between 9 and 18 km in depth is less than the minimum of 6-5 krnysec generally found elsewhere; but to ascribe the source of the gravity deficiency to this layer would imply a reduction of its density by at least 0-55 g/cm 3 • For New Zealand earthquakes, Eiby (1958) has reported a wide variation in the Pn velocity above and below the «normal" 8 krnysec, but there is no suggestion of consistently low values.…”
Section: Crustal Thickness Fro~1 Gravity Datasupporting
confidence: 60%
“…The reduction of this figure would demand either a reduction of the mean density of (he crust by at least 0-3 g/cm 3 , or a comparable reduction of the mean density within the upper mantle. However, the longitudinal wave velocities in the upper part of the crust as well as P n for the material immediately below the crust appear to be similar to those found in other continental areas of rhe world, though the velocity of 6-2 krnysec for Eiby's «intermediate" layer lying between 9 and 18 km in depth is less than the minimum of 6-5 krnysec generally found elsewhere; but to ascribe the source of the gravity deficiency to this layer would imply a reduction of its density by at least 0-55 g/cm 3 • For New Zealand earthquakes, Eiby (1958) has reported a wide variation in the Pn velocity above and below the «normal" 8 krnysec, but there is no suggestion of consistently low values.…”
Section: Crustal Thickness Fro~1 Gravity Datasupporting
confidence: 60%
“…He observed that the Pn velocity is higher (8' 3 krn/s) along paths to the south-west of the epicentre of the 1966 Gisborne earthquake than it is along paths to the west (7'7km/s) and north-west (7·8km/s). In view of the average velocity of 8· 1 km/s found previously (Bullen 1939;Eiby 1958;Hamilton 1966), he interprets this difference as being possibly due to anisotropy.…”
mentioning
confidence: 48%
“…The volcanic belt closely parallels the "sub-crustal rift" defined by Eiby (1959) on the basis of earthquake epicentres, but there is a marked absence of focal depths less than 100 km (pers. comm., Mr G. A.…”
Section: Geologymentioning
confidence: 99%